2013
DOI: 10.1002/qj.2142
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of an MCS over southern England. Part 2: Model simulations and sensitivity to microphysics

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Convection and the RIJ formed during the model spin‐up period so it was not possible to investigate the initiation from these simulations, but tests showed that diabatic cooling enhanced the RIJ (consistent with Yang and Houze, ; Braun, ; Braun and Houze, ; Franklin et al ., ; Clark et al ., ). During the spin‐up period, diabatic cooling enhanced the undercurrent, and once the MCS formed the cooling enhanced the RIJ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Convection and the RIJ formed during the model spin‐up period so it was not possible to investigate the initiation from these simulations, but tests showed that diabatic cooling enhanced the RIJ (consistent with Yang and Houze, ; Braun, ; Braun and Houze, ; Franklin et al ., ; Clark et al ., ). During the spin‐up period, diabatic cooling enhanced the undercurrent, and once the MCS formed the cooling enhanced the RIJ.…”
Section: Discussionmentioning
confidence: 99%
“…() and Clark et al . (), who all found that removing latent cooling either prevented or significantly weakened cold pool formation.…”
Section: The Dependence Of the Mcs On Selected Physical Processesmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have shown that both WSP (Chong, ; Clark et al, ; Innocentini & Neto, ; Kingsmill et al, ; Lin et al, ) and CFP (Bodine & Rasmussen, ) are mainly produced by MCSs, which themselves are greatly affected by cloud microphysical processes. In this part, we begin by discussing the microphysical and thermodynamic vertical structures of MCSs in the WSP and CFP.…”
Section: Probable Mechanism For Wsp and Cfp In Terms Of Cloud Microphmentioning
confidence: 99%
“…The objectives of the article are to elucidate the observed structure of the MCS and how it changed in time, particularly focussing on a major transition period. Model simulations of the event are presented in Clark et al (2013), referred to as Part 2 hereafter, to gain some insight into the processes contributing to this structure, with particular emphasis on the contribution from different microphysical processes.…”
Section: Introductionmentioning
confidence: 99%